The relationship between facial negative physical self and social anxiety in college students: the role of rumination and self-compassion - Yan, Yuxian; Zhou, Xinyu; Zhou, Jinhui; Chen, Yin; Zhang, Yan; Zhou, Xin; Luo, Jiaming (Frontiers in Psychology, 2025)
BackgroundTo investigate the association between facial negative physical self, social anxiety, rumination, and self-compassion among college students in western China.MethodsA questionnaire was used to conduct an online survey of 1, 178 students from a university in western China through convenience sampling using the Self-Compassion Scale, the Ruminative Response Scale, the Negative Physical Self Scale-facial appearance sub-scale and the Interaction Anxiousness Scale.ResultsIn the mediation model, the total predictive effect of facial negative physical self on social anxiety was significant (B = 0.46, t = 17.66, p < 0.01), and the mediating effect of facial negative physical self on social anxiety accounted for 48. 1% of the total effect; self-compassion moderated the effect of rumination on social anxiety (B = –0.06, t = 3.00, p < 0.01).ConclusionFacial negative physical self affects the level of social anxiety of college students through rumination, and self-compassion regulates the effect of rumination on social anxiety. Students should be encouraged to increase their level of self-compassion or be provided with self-compassion intervention training, which can help reduce social anxiety.